The Abyss of the Unknown in the Books “The Fall of the House of Usher” and “A Rose for Emily” - Matta, May (European Scientific Journal, ESJ, 2018)
The stories “The Fall of the House of Usher” and “A Rose for Emily” have made an important contribution to literature. “The Fall of the House of Usher” presents a story of a family consisting of two siblings who lived together in an isolated house. Similarly, “A Rose for Emily” presents the story of a woman, Emily who lived a mysterious life. There are various themes that can be drawn from the stories. The aim of this paper is to explore the universal theme of the abyss of the unknown in the two stories. Thus, the paper critically delves into the elements of the stories that support the theme. Some of the supporting themes in “The Fall of the House of Usher” include the house, terror, illness and madness, the description of the family, and death. In “A Rose for Emily”, the presented themes are resistance to change, family, death, and alienation. The paper also analyzes the similarities and dissimilarities as presented in the stories with regard to the universal theme. The similarities include families and residences, incest, house, isolation, and the deaths of the characters. The dissimilarities in the stories were in the setting of the stories and suspense.